# If p(x) = x + 3, then p(x) + p(-x) is equal to

a. 3

b. 2x

c. 0

d. 6

**Solution:**

It is given that

p(x) = x + 3

We have to find the value if p(x) + p(-x)

Here p(-x) = -x + 3

p(x) + p(-x) = x + 3 + (-x + 3)

So we get

p(x) + p(-x) = x + 3 - x + 3

p(x) + p(-x) = 6

Therefore, p(x) + p(-x) is equal to 6.

**✦ Try This: **If p(x) = x + 5, then p(x) + p(-x) is equal to

It is given that

p(x) = x + 5

We have to find the value if p(x) + p(-x)

Here p(-x) = -x + 5

p(x) + p(-x) = x + 5 + (-x + 5)

So we get

p(x) + p(-x) = x + 5 - x + 5

p(x) + p(-x) = 10

Therefore, p(x) + p(-x) is equal to 10.

**☛ Also Check: **NCERT Solutions for Class 9 Maths Chapter 2

**NCERT Exemplar Class 9 Maths Exercise 2.1 Problem 7**

## If p(x) = x + 3, then p(x) + p(-x) is equal to a. 3, b. 2x, c. 0, d. 6

**Summary:**

The highest sum of the exponents is known as the degree of a polynomial. If p(x) = x + 3, then p(x) + p(-x) is equal to 6

**☛ Related Questions:**

Math worksheets and

visual curriculum

visual curriculum